Les relations culturelles germano-américaines, pierre angulaire de la politique américaine de sécurité en Europe dans les années 1980 - Maud QUESSARD-SALVAING (Cahiers du MIMMOC)
Maud Quessard works on Soft power and US public diplomacy. Her contribution focuses on the German-American relations of the 1980s that were a priority for Reagan’s American diplomacy and remained at the center of Cold War issues. Studying those relationships enable the identification of two types of soft power strategies: those of crisis or Cold War that require immediate pragmatic responses, and on the other hand those of the long term, that involve exchanges and interpersonal relationships. The author shows in particular how “long, operational and structural timing” that characterizes public diplomacy, as well as the strategies implemented by US information officers, differs from the “short timing” of pragmatic reactions to international economic, military or political crises.